PENGGUNAAN PEMBELAJARAN ASSURE UNTUK MENINGKATKAN MOTIVASI DAN NILAI SISWA DALAM BELAJAR PKn DI KELAS IV-B SDN JENGGAWAH 01KEC. JENGGAWAH JEMBER SEMESTER GASAL TAHUN 2012/2013 - Wirastuti Setyaningsih (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2014)
Based on the previous description, the research problems emerged: (1) How does the implementation of ASSURE learning model to Increase the Students’ Motivation and Learning Outcome in learning civic education (PKn) for the students of class IV-B SDN Jenggawah 01 in odd semester in the academic year 2012/2013?; and (2) Is the implementation of ASSURE learning model able to increase the Students’ Motivation and Learning Outcome in learning civic education (PKn) for the students of class IV-B SDN Jenggawah 01 in odd semester in the academic year 2012/2013?.  This study aims to (1) Describe  the implementation of ASSURE learning model to Increase the Students’ Motivation and Learning Outcome in learning civic education (PKn) for the students of class IV-B SDN Jenggawah 01 in odd semester in the academic year 2012/2013; and (2) find out the implementation of ASSURE learning model can increase the Students’ Motivation and Learning Outcome in learning civic education (PKn) for the students of class IV-B SDN Jenggawah 01 in odd semester in the academic year 2012/2013. This researcher conducted a classroom action research (CAR). The subject of this study is the fourth grader students of SDN Jenggawah 01. Observation, interview, test, and questioner are the methods in collecting the data. Descriptive qualitative is employed to analyze the data.  The research findings show that it is through the implementation of ASSURE learning model the students’ motivation and learning outcomes in civic education (PKn) for the fourth grader (IV-B) of SDN Jenggawah 01 in odd semester in the academic year 2012/2013 has significantly increased.Keywords:ASSURE learning model, motivation, learning outcome.